ΤΟΠΩΝΥΜΙΚΑΙ ΔΙΑΣΑΦΗΣΕΙΣ Ι. ΜΥΟΝΝΗΣΟΣ - ΠΡΟΜΠΟΝΑΣ ΙΩΑΝΝΗΣ Κ. (Μνήμων, 1972)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> Δεν παρατίθεται περίληψη. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>